WORK ENVIRONMENT, JOB SATISFACTION AND EMPLOYEE PERFORMANCE IN HEALTH SERVICES - Abdul Haeba Ramli (Universitas Trisakti, 2019)
This investigation point is to appraise the work environment, job satisfaction and the employees performance of Rumah Sakit Swasta in Jakarta. The point is also to appraise the phenomenon of the work environment, on the job satisfaction and its involvement to the employees performance of Rumah Sakit Swasta in Jakarta. The investigation is using the quantitative investigation.. The sample for data collection was taken from 82 employees of Rumah Sakit Swasta in Jakarta through questionnaires. From the investigation done, it is demonstrated that the work environment has positive effect toward the job satisfaction and employee’s performance, and job satisfaction do have a positive involvement on the employee’s performance of Rumah Sakit Swasta in Jakarta.